The Response of Foxtail Millet Candidate Varieties from Nagekeo Regency to Leaf Blight (Bipolaris setariae) - Suriani Suriani; Amran Muis; Septian Hary Kalqutny (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Foxtail millet has the potential to be developed as a healthier food alternative because of its high nutritional value. Disease such as leaf blight caused by Bipolaris setariae is one of the limiting factors in Foxtail millet productivity. One of the efforts to control the pathogen is by utilizing resistant varieties. In this study, two candidate varieties and two germplasm accessions were tested to determine the level of resistance to Bipolaris setariae leaf blight. The study was arranged based on a complete randomized design with six replications. Each test material was inoculated with the spore suspension at 4 WAP. Disease intensity was observed based on the disease scoring at 7, 9, and 11 WAP. AUDPC value is calculated based on the intensity of the attack at a particular observation time. Grain weight was recorded and statistically analyzed. The two candidate varieties of foxtail millet Pagamogo and Tedamude from Nagekeo Regency showed a moderately resistant response to leaf blight and had the lowest AUDPC values of 907.69 and 912.31. The highest increase in AUDPC values was observed in the initial observation period at 0-49 DAP.